PERSEPSI MAHASISWA TENTANG LAYANAN PERKULIAHAN MAHASISWA DI PRODI PENDIDIKAN EKONOMI FKIP UNTAN - yarso, Wendo; Asriati, Nuraini; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrakThis study aims to determine the level of student satisfaction with lecturing services at the FKIP UNTAN Pontianak Economic Education Study Program. The form of this research is using descriptive method. The technique used is the distribution of questionnaires to customers (students) as research samples and tracking documentation. Based on data analysis Student responses about reliability services 35.0% are in accordance with 5.0% very appropriate, there are 40.0% less appropriate, responsiveness can be said to be very low there are 52.0% of respondents that responsiveness is less appropriate, 8.0% is not appropriate. While only 18.0% are appropriate. Assurance can be said to be 61.0% that the elements of Guarantee are appropriate only 1.0% are not appropriate and 15.0% are not appropriate, empathy can be said to be still lacking and needs to be improved because 63.0% of respondents based on quality based on empathy are not suitable and another 19.0% are not appropriate. While the other 20.0% are suitable and 8.0% are very suitable. Physical evidence can be said to be lacking this can be seen that the majority of respondents (53%) in the form of physical evidence are less appropriate.Â Keywords: Assurance, Empathy, Reliability, Responsiveness, Service QualityÂ